Maternal health care wearing equipment based on fetal information monitoring - Junyan Peng; Yicheng Huang; Kanbin Yu; Renjie Fan; Jia Zhou (Elsevier, 2020)
In order to monitor the fetal information in real time and ensure the health of the pregnant women themselves and their fetuses during pregnancy, a kind of health wearing equipment, abdominal care belt is designed in this study, which can be worn by pregnant women and can be monitored by modern mobile medical APP, and verifies the related performance of the design through a series of experiments. The results show that the safety, practicability and aesthetics of the abdominal care belt designed in this study are all up to the standard. Therefore, the abdominal care belt designed in this study is a relatively successful product, which is expected to be applied in the future and enter the market, so that pregnant women during pregnancy can be more relaxed and convenient.